The Difference of Clinical Characteristic COVID-19 patient with Vaccinated and Unvaccinated - Iin Novita Nurhidayati Mahmuda; Azarine Marwah (Universitas Muhammadiyah Malang, 2023)
Coronavirus disease or COVID-19 was first discovered in Wuhan, China and spreads through respiratory droplet transmission with various clinical characteristics that are often encountered such as fever and cough, shortness of breath, myalgia and nausea/vomiting according to the severity of COVID-19 patients. The severity of clinical characteristics in COVID-19 patients can be influenced by factors of age, comorbidities, gender, immunocompromised status, occupation (healthworkers), and vaccination status. This research is for knowing the differences in the clinical characteristics of vaccinated and unvaccinated COVID-19 patients at University of Muhammadiyah Surakarta students. This study uses an observational analytic study with a cross-sectional approach and was carried out on students at the University of Muhammadiyah Surakarta who were confirmed to have COVID-19 using a google-form questionnaire as primary data. Data were analyzed using chi-square test. The symptoms of COVID-19 such as fever, cough, common cold, myalgia, anosmia or rash did not show a significant difference. Meanwhile, the symptoms of nausea/vomiting were found in individuals who had not been vaccinated more than individuals who had been vaccinated (p = 0.002). There was no significant difference in clinical characteristics of COVID-19 patients who had been vaccinated or had not been vaccinated, except for complaint of nausea/vomiting.